Marble networks: Social interaction in houses at Pompeii - Barker, Simon J.; Perna, Simona; Ward, Courtney A. (Archaeological Networks and Social Interaction, 2020)
This chapter explores the link between marble use in Roman domestic contexts and social ties through social network analysis. The use of imported marble as a decorative material is almost synonymous with elite status display in the Roman world. The importance of marble decoration in Roman domestic contexts is evident from the display of both real and painted imitation marble at sites around the Bay of Naples like Pompeii, Herculaneum, Oplontis and Stabiae. Here, well-preserved pavements from the first century BCE to the first century AD feature marbles from all over the Mediterranean and Egypt’s Eastern Desert. Marble is a visual object –visibility is a central feature of its social significance, thus a key element in aiding its spread via social interaction. As such, this chapter seeks to understand to what extent and in what ways social relations impacted the spread of domestic marble decoration in the Roman town of Pompeii.
Keywords: #nosource; /unread